Performance of tubular T-joints at elevated temperature by considering effect of chord compressive stress. (January 2016) - Shao, Yongbo; Zheng, Yijie; Zhao, Haicheng; Yang, Dongping
Abstract: This paper aims to study the performance of welded circular tubular T-joints subjected to axial compressive loads at the ends of both the brace and the chord at elevated temperature. Different from previous studies on circular hollow section (CHS) T-joints under brace axial load at elevated temperature, the effect of the chord stress is also taken into consideration. Overall six specimens are designed and tested in an environment in accordance with ISO 834 heating process. Different levels of compressive loads are applied in the axial direction of the chord to investigate their effect on the fire resistance of the specimens. Temperature development at some critical positions around the brace/chord intersection is measured during experimental test. The developments of defined global and local deformations during heating process are also obtained. The failure modes of all specimens are found to be characterized by chord plastification around the brace/chord intersection. By introducing an elastic modulus reduction factor and a yield strength reduction factor, the feasibility of some equations provided by Eurocode EN 1993-1-2, CIDECT and API RP 2A WSD for calculating the static strength of the specimens at elevated temperature are evaluated based on the experimental results. Highlights: CHS T-joints with chord compressive stress at elevated temperature were tested. Effect of chord compressive stresse on failure process of T-joints was analyzed. Static strengths of T-joints at elevated temperatures were compared with revised equations.